The Exploration of Risk and Protective Score Differences Across Juvenile Offending Career Types and Their Effects on Recidivism - Cox, Stephen (Youth violence and juvenile justice, 2018)
Despite an abundance of research on serious and violent juvenile offenders, few studies have linked juvenile offending career categories to juvenile court risk assessments and future offending. This study uses juvenile court referrals and assessment data to replicate earlier categorizations of serious, violent, and chronic offenders; to examine risk and protective score differences across these categories; and to assess whether risk and protective score constructs differentially predict adult criminality across these offender categories. Based on a sample of 9,859 juvenile offenders who aged out of Connecticut’s juvenile justice system between 2005 and 2009, we found that (1) our categorization of juvenile career types mirrored earlier work, (2) comparing risk and protective factors across and within juvenile career types identified distinct patterns, and (3) the juvenile risk and protective assessment subscales were not predictive of adult arrests for chronic offenders but were predictive for nonchronic juvenile career types.